THE ALL OF LAWSUITS (ONSLAAG VAN ALLE RECHTSVERVOLGING) IN THE CRIME OF CORRUPTION - Renggong, Ruslan (Journal of Humanity, 2013)
The verdict from all lawsuits (onslaag van alle rechtsvervolging) dropped the judge to the defendant in this matter can be categorized as progressive verdicts when associated with corruption eradication efforts. At a time when the Government was determined to eradicate corruption, still popping Awards judge who frees or releasing the accused. In the case when the prosecution claim is examined in depth and is associated with the fact at the trial the accused should have been convicted of a criminal offence of corruption and very worthy was sentence to criminal penalties. The purpose of criminals, ruling out of any law against judges not bring deterrent effect for want to be corruptor.